Validation of Elemental and Isotopic Abundances in Late-M Spectral Types with the Benchmark HIP 55507 AB System - Jerry W. Xuan; Jason Wang; Luke Finnerty; Katelyn Horstman; Simon Grimm; Anne E. Peck; Eric Nielsen; Heather A. Knutson; Dimitri Mawet; Howard Isaacson; Andrew W. Howard; Michael C. Liu; et al. (The Astrophysical Journal, 2024)
M dwarfs are common host stars to exoplanets but often lack atmospheric abundance measurements. Late-M dwarfs are also good analogs to the youngest substellar companions, which share similar T _eff ∼ 2300–2800 K. We present atmospheric analyses for the M7.5 companion HIP 55507 B and its K6V primary star with Keck/KPIC high-resolution ( R ∼ 35,000) K -band spectroscopy. First, by including KPIC relative radial velocities between the primary and secondary in the orbit fit, we improve the dynamical mass precision by 60% and find ${M}_{B}={88.0}_{-3.2}^{+3.4}\,M_{Jup}$ , putting HIP 55507 B above the stellar–substellar boundary. We also find that HIP 55507 B orbits its K6V primary star with $a={38}_{-3}^{+4}$ au and e = 0.40 ± 0.04. From atmospheric retrievals of HIP 55507 B, we measure [C/H] = 0.24 ± 0.13, [O/H] = 0.15 ± 0.13, and C/O = 0.67 ± 0.04. Moreover, we strongly detect ^13 CO (7.8 σ significance) and tentatively detect ${{\rm{H}}}_{2}^{18}{\rm{O}}$ (3.7 σ significance) in the companion’s atmosphere and measure ${}^{12}CO{/}^{13}CO={98}_{-22}^{+28}$ and ${{\rm{H}}}_{2}^{16}{\rm{O}}/{{\rm{H}}}_{2}^{18}{\rm{O}}={240}_{-80}^{+145}$ after accounting for systematic errors. From a simplified retrieval analysis of HIP 55507 A, we measure ${}^{12}CO{/}^{13}CO={79}_{-16}^{+21}$ and ${{\rm{C}}}^{16}{\rm{O}}/{{\rm{C}}}^{18}{\rm{O}}={288}_{-70}^{+125}$ for the primary star. These results demonstrate that HIP 55507 A and B have consistent ^12 C/ ^13 C and ^16 O/ ^18 O to the <1 σ level, as expected for a chemically homogeneous binary system. Given the similar flux ratios and separations between HIP 55507 AB and systems with young substellar companions, our results open the door to systematically measuring ^13 CO and ${{\rm{H}}}_{2}^{18}{\rm{O}}$ abundances in the atmospheres of substellar or even planetary-mass companions with similar spectral types.